2021
DOI: 10.3390/molecules26175310
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals in Immune Function

Abstract: Nutraceutical, a term derived from ‘nutrition’ and ‘pharmaceutical’, refers to any product isolated from herbs, nutrients, specific diets, processed foods, and beverages used not only for nutritional but also for medicinal purposes [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…They can be delivered as dietary supplements or functional food, providing bene cial effects and essential nutritional components. Several studies have demonstrated the signi cant bene cial effects of nutraceuticals on immune system functions, such as boosting immunomodulatory activity and reducing the impacts of autoimmune disorders and hypersensitivity [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…They can be delivered as dietary supplements or functional food, providing bene cial effects and essential nutritional components. Several studies have demonstrated the signi cant bene cial effects of nutraceuticals on immune system functions, such as boosting immunomodulatory activity and reducing the impacts of autoimmune disorders and hypersensitivity [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The published studies suggest that the use of nutraceuticals may improve the immune system and decrease the likelihood of some diseases such as cold, flu, anxiety, depression, cardiovascular diseases, etc. [ 65 , 66 , 67 , 68 , 69 ]. The neurological complications can be exacerbated in co-infection of HIV and COVID-19 due to the ineffectiveness of ARTs.…”
Section: Covid-19-associated Neurological Complicationsmentioning
confidence: 99%
“…Nutraceuticals are natural substances derived from edible sources that confer health benefits beyond their nutritional values [10]. Unlike synthetic molecules, which are typically flat and straightforward, naturally occurring compounds often contain enormously diverse and complex molecules [11].…”
Section: Introductionmentioning
confidence: 99%